New potential carbon source for bioprotein production - Jamal, Parveen; Alam, Md. Zahangir; Tompang, Mohamad Fahrurrazi (2008)
Screening study was done to obtain the most potential substrate from agricultural wastes such as pineapple, honeydew and durian skins as main carbon source for bioprotein production utilizing potential strain of P. chrysosporium (PC 13) by liquid state bioconversion. In this study, two different media conditions have been used for selected substrate, which were fermentation without additional nutrient (WON) and with additional nutrient (WN) as to investigate the effect of wheat flour concentration as co-substrate on the bioprotein production. This study showed a promising result with improved protein for selected potential substrate, pineapple skins without wheat flour as a co-substrate, has produced 16.8 g L-1 biomass and 72.9 g kg-1 protein with 9.38 mg ml-1 initial sugar in fermentation at controlled process conditions of temperature of 32 °C; agitation of 150 rpm and pH 4.5. Bioprotein from local agro-waste can be a good source of supplement and additive in the animal feed as well as additives in the chemical and pharmaceutical products.